2010
DOI: 10.1002/eat.20683
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between body mass index and television viewing, internet use and cellular phone use: The moderating effects of socio‐demographic characteristics and exercise

Abstract: The results support the relationships between adolescent BMI and television viewing and Internet use. The moderating effect of exercise and various Internet and cellular phone-related activities should be considered when developing intervention strategies for overweight adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 37 publications
(40 reference statements)
2
47
1
1
Order By: Relevance
“…Interestingly, not all sedentary behavior has the same potential to increase the risk of obesity. According to Yen (Yen et al, 2010) adolescents who had high television viewing had higher BMI after controlling for the effects of socio-demographic characteristics and exercise level. While the associations between BMI and television viewing and exercise level became insignificant, the interaction between television viewing and exercise level was significantly associated with BMI.…”
Section: Television Watchingmentioning
confidence: 91%
See 4 more Smart Citations
“…Interestingly, not all sedentary behavior has the same potential to increase the risk of obesity. According to Yen (Yen et al, 2010) adolescents who had high television viewing had higher BMI after controlling for the effects of socio-demographic characteristics and exercise level. While the associations between BMI and television viewing and exercise level became insignificant, the interaction between television viewing and exercise level was significantly associated with BMI.…”
Section: Television Watchingmentioning
confidence: 91%
“…In 1985 the first assertion that television viewing may lead to obesity in some children and adolescents was published (Dietz & Gortmaker, 1985). The authors reported that the prevalence of obesity in adolescents increased 2% for each additional hour of television watched (Yen et al, 2010). They suggested that this relationship may be mediated by a direct displacement of physical activity, as well as, an increase in caloric consumption induced by food advertisements and snacking time (Dietz & Gortmaker, 1985).…”
Section: Television Watchingmentioning
confidence: 99%
See 3 more Smart Citations